Surgical Atlas of Cardiac Anatomy - Zhu, Xiaodong; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This Atlas is illustrated with rich pictures of cardiac surgical specimens. It not only contains normal heart specimens but also dissects those specimens, taking pictures from various angles to create a three-dimensional representation. It also includes reviews of the specimens$1 (Bpathological reviews. Chapter 1 through 10 introduce the normal anatomy of the cardiac chambers and surgical approaches to the heart, while chapter 11 through 28 describe 18 kinds of congenital heart defects. There are a total of over 1,000 images and illustrations in this book, which will be of great interest not only to the surgeons, but also to the cardiologists, anaesthesiologists and surgical pathologists. Editor Xiaodong Zhu is professor and former dean of Fuwai Hospital, Chinese Academy of Medical Science and Peking Union Medical College. He is an academician of the Chinese Academy of Engineering.s
Cardiac Anatomy: Nomenclature and Abbreviations -- Position and Observation of the Heart and Surgical Approaches -- The Right Atrium -- The Right Ventricle -- The Coronary Artery -- The Conduction System of the Heart -- The Left Atrium -- The Left Ventricle -- The Cardiac Skeleton and the Aortic Root -- General Considerations of Cardiac Embryology -- Atrial Septal Defect and Cor Triatriatum -- Atrioventricular Septal Defect -- Ventricular Septal Defect -- Anomalous Pulmonary Venous Drainage -- Aortic Arch Coarctation and Interrupted Aortic Arch -- Congenital Anomalies of the Tricuspid Valve -- Right Ventricular Outflow Tract Obstruction -- Mitral Atresia and Hypoplastic Left Ventricle -- Single Ventricle -- Persistent Truncus Arteriosus -- Aortopulmonary Window -- Aneurism of the Sinus of Valsalva -- Tetralogy of Fallot -- Double Outlet Right Ventricle -- Complete Transposition of the Great Arteries -- Corrected Transposition of the Great Arteries -- Pulmonary Atresia -- Double-outlet of Left Ventricle.
Keywords: Medicine; Human anatomy; Cardiology; Cardiac surgery; Medicine & Public Health; Cardiac Surgery; Anatomy; Cardiology; Electronic books